THE IMPACT OF THE BOARD OF DIRECTORS’ EXPERIENCE, EDUCATION, AND COMPENSATION ON INDONESIAN BANKS’ FINANCIAL PERFORMANCE - Sriwati , Sriwati; Verawati , Verawati; Kurniawan, Herni (International Journal of Application on Economics and Business, 2025)
The company's governance enables it to be regulated and overseen in order to adhere to the law, stakeholder expectations, and relevant business ethics and standards. For the firm to survive and prosper in the long run, the board of directors, which makes the majority of the decisions, chooses the company's strategic course. As a result, in order to motivate the board of directors to enhance financial performance, it is essential to secure their wellbeing by paying them. In addition to salary, the board of directors' expertise and education in business and finance are probably going to be a factor in enhancing Indonesian banks' financial performance. The aim of this study is to demonstrate empirically the relationship between the financial performance of Indonesian banks and the board of directors' experience, business and financial education, and salary. The research sample consists of banking businesses from 2019 to 2023, and the research methodology is quantitative description utilizing annual report data. The Eviews-12 software tool aids in this study by generating 155 observation data that can be processed. According to the study's findings, the bank's financial performance has been demonstrated to be improved by the board of directors' salary. The business and financial education of the board of directors cannot enhance or detract from the bank's financial performance. The same results have been shown by the board of directors' experience, which can enhance the bank's financial performance.